Green Oil - An investigation of the environmental narratives of ‘Profits & Principles’ - Gadd,Dorian (2025)
This paper examines the ways in which carbon majors like Shell may present and identify themselves as ‘green’ alternatives whilst undermining the credibility of climate change science by investigating the construction of these narratives and how they differ between internal (employees) and external (general public) audiences. Focus is paid primarily to their rebranding of the late 1990s, analysing the corporate social responsibility reports published at this time alongside internal reviews of climate science, which are further contrasted with an earlier, confidential review detailing climate change, accessible only to Shell leadership. It finds that, whilst the confidential report leaves little room to doubt the greenhouse effect and fossil fuel’s contribution, Shell carefully constructs both its employees and the general public to accept climate change as an issue yet uncertain whilst simultaneously maintaining a facade of genuine inquiry. However, where such uncertainties are emphasised almost to the degree of paralysis in internal material, the external material seem to underscore a need for preemptive measures, ‘just in case’ — measures which they also know to be insufficient. Though this might seem contradictory, by using Fooks et al.’s (2013) three-step model of corporate response to declining political authority, it becomes clear that they are simply two different steps of the same process, conveying the image of Shell as a company that cares.
Keywords: Greenwashing; Techniques of Neutralisation; Corporate Discourse; Corporate Social Responsibility; Corporate Environmental Communications